Steroid avoidance or withdrawal after renal transplantation increases the risk of acute rejection but decreases cardiovascular risk. A meta-analysis. - Knight, SR; Morris, P (2010)
INTRODUCTION: The morbidity related to long-term steroid therapy has led to continued interest in withdrawal of steroids from immunosuppressant regimens after renal transplantation. A number of recent trials have provided long-term information regarding the risks and benefits of steroid avoidance or withdrawal (SAW). METHODS: A literature search was performed using Ovid Medline, Embase, the Cochrane Library, and the Transplant Library. Randomized controlled trials comparing a maintenance steroid group with complete avoidance or withdrawal of steroids were selected. All studies were assessed for methodological quality. Trials were pooled by meta-analysis to provide summary effects (relative risk [RR] or weighted mean difference) with 95% confidence intervals (CI). RESULTS: Thirty-four studies including 5,637 patients met the inclusion criteria. SAW regimens significantly increased the risk of acute rejection (AR) over maintenance steroids (RR 1.56, CI 1.31-1.87, P<0.0001). No significant differences in corticosteroid resistant AR, patient survival, or graft survival were observed. Serum creatinine was increased and creatinine clearance was reduced with SAW. Cardiovascular risk factors including incidence of hypertension (RR 0.90, CI 0.85-0.94, P<0.0001), new onset diabetes (RR 0.64, CI 0.50-0.83, P=0.0006), and hypercholesterolemia (RR 0.76, CI 0.67-0.87, P<0.0001) were reduced significantly by SAW. CONCLUSION: Despite an increase in the risk of AR with SAW protocols, there is only a small effect on graft function with no measurable effect on graft or patient survival. There are significant benefits in cardiovascular risk profiles after SAW. SAW protocols would seem justified with current immunosuppressive protocols in low-risk recipients.